Implementasi Kurikulum Merdeka pada Projek Penguatan Profil Pelajar Pancasila di Madrasah Tsanawiyah Negeri 1 Banyumas - Aurora Eksata Putri; Nurfuadi Nurfuadi (An-Nahdloh: Journal of Education and Islamic Studies, 2026)
This research aims to deeply describe and analyze the implementation of the Independent Curriculum, specifically focusing on the Strengthening Project of the Pancasila Student Profile (P5) which is integrated with the value of Rahmatan Lil 'Alamin at State Islamic Junior High School 1 Banyumas (Madrasah Tsanawiyah Negeri 1 Banyumas). The Independent Curriculum was introduced as a post-COVID-19 educational reform effort, emphasizing the development of student character and competence through project-based learning. Within the context of a madrasah, this is realized through P5RA, which harmoniously integrates Islamic and national values. MTsN 1 Banyumas was selected as the research location because it is one of the pilot projects for implementing the Independent Curriculum. This study uses descriptive qualitative field research, with data collected through observation, interviews, and documentation. The findings indicate that the implementation of the Independent Curriculum through the Pancasila Student Profile strengthening project proceeded smoothly and successfully through a number of projects. The project implementation was carried out in a series of stages: 1) preparing the madrasah ecosystem by actively involving students in madrasah activities and fostering student capacity through training and workshops; 2) planning P5 which consists of forming a project implementation team, identifying the madrasah's readiness, determining the thematic dimensions and time allocation, and creating project modules; 3) implementing P5 which covers introduction, contextualization, action, reflection and follow-up, and a final celebration of the results; 4) processing assessment and reporting P5 outcomes including data collection, data processing, and preparing project report cards; and 5) P5 evaluation and follow-up in the form of character strengthening, continuing good practices, project sustainability, and establishing cooperation with external partners. Through P5, it is effective in fostering the six dimensions of the Pancasila Student Profile in students, including belief in God Almighty and noble character, global diversity (Kebhinekaan Global), communal work (Gotong Royong), independence, critical reasoning, and creativity. Kata Kunci: Independent Curriculum, Strengthening Project of the Pancasila Student Profile (P5), State Islamic Junior High School